1993
DOI: 10.1152/ajpgi.1993.265.4.g799
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of CO on internal anal sphincter: heme oxygenase inhibitor inhibits NANC relaxation

Abstract: We examined the effect and role of CO in opossum internal anal sphincter (IAS) relaxation in response to nonadrenergic noncholinergic (NANC) nerve stimulation. Effects of NANC nerve stimulation on the IAS tension and second messengers (cAMP and cGMP) were examined before and after the selective heme oxygenase (HO) inhibitor zinc protoporphyrin IX (Zn PP-IX). The HO activity of the IAS smooth muscle was determined before and after NANC nerve stimulation. CO caused a concentration-dependent and tetrodotoxin-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 0 publications
7
86
1
Order By: Relevance
“…Previous studies have shown that CO could regulate nonadrenergic/ noncholinergic intestinal relaxation (50,68), intrahepatic vascular resistance (58), pulmonary vascular resistance (59), and relaxation of tail artery tissues (66). Exogenously delivered CO has exerted potent protective functions in numerous experimental models of inflammation, sepsis/endotoxemia, hemorrhagic shock, autoimmune diseases, and fibrosis (7,18,52,57,65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CO could regulate nonadrenergic/ noncholinergic intestinal relaxation (50,68), intrahepatic vascular resistance (58), pulmonary vascular resistance (59), and relaxation of tail artery tissues (66). Exogenously delivered CO has exerted potent protective functions in numerous experimental models of inflammation, sepsis/endotoxemia, hemorrhagic shock, autoimmune diseases, and fibrosis (7,18,52,57,65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Recent observation by Rich et al has provided evidence that CO elicits an increase in potassium current and thereby hyperpolarizes the resting membrane potential in rabbit corneal epithelial cells (29). Since the hyperpolarizing effects of CO has also been reported in other types of cells such as intestinal smooth muscle cells (30), electrophysiological properties of cultured Ito cells and the effect of CO on transmembrane currents should be evaluated to reveal a novel vasorelaxing mechanism of CO. Moreover, since sinusoidal endothelial cells per se may serve as another possible contractile element which alters fluid filtration via regulation of tone in their sieve plates (31), it is also necessary to elucidate involvement of such Ito cell-independent mechanisms for CO-mediated regulation of sinusoidal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The SMCs from the IAS and RSM were isolated by a previously described method (27,32) using sequential enzymatic digestion, filtration, and centrifugation. Briefly, the smooth muscle tissues cut into 0.2 ϫ 0.2 mm blocks were incubated in filtered (0.22-m filter) KPS containing 0.1% collagenase and 0.01% trypsin inhibitor.…”
Section: Methodsmentioning
confidence: 99%